THE DESIGN OF HEALTH OF PERSONS WITH KNEE OSTEOARTHROSIS (GONARTHROSIS ) AND ITS CORRELATION WITH THE PRINCIPAL RISK FACTORS . (Fiep Bulletin - online, 2014)
Currently there is an increase in life expectancy and the aging population , which has been changing the health demands and revealing a greater concern with the chronic degenerative diseases . This research sought to understand the concept of health for people with knee osteoarthritis ( KOA ) who attended the physiotherapy clinic at the University of Vale do Itajaí , knowing the main risk factors , relating these factors to the symptoms , and proposing a program of Education in Health research used was qualitative , semi -structured interviews with open questions and , based on Convergent Care Research . We interviewed 10 patients with OAJ . The average age was 65.5 years and mean weight 79.04 kg , mean BMI 33.38 . As for smoking habits , never smoked 4 , 4 stopped more than 10 years and 2 still smoke . On the knowledge of the pathology of patients , it was observed that there is a failure in regard to clarify the diagnosis and exchange among healthcare staff and patients. In this study, four participants with health related pain. For six of health related to daily activities without restrictions . Another important fact is that for eight of the participants , the weight gain was considered as a factor in worsening symptoms . All objectives were achieved , it is possible to meet in full the people diagnosed with OAJ , could know and define the risk factors, symptoms , knowledge of the disease and how this interferes with your life .
Keywords: Osteoarthritis Knee; Physiotherapy and Health Education